Creative Story through 9GAG Application in Teaching Speaking - Hadi, Muhamad Sofian; Zaitun, Zaitun; Suni, Tsamara Fairuz (JOLLT Journal of Languages and Language Teaching, 2021)
This study aims to improve students’ speaking abilities through creative stories using the 9GAG application. The study is a quantitative method with Quasi-Experimental design. Speaking tests are employed as research instruments in collecting the data. The researchers used two classes of the ninth grade of MTs Al-Islamiyah, Tangerang for the population. The sampling technique used was cluster sampling in which the 9.4 class was determined as the experimental class and the 9.5 class as the control class. The data was analyzed statistically by using a t-test to find out the significant difference. The result of this analysis indicated that the average value of the students was 70.33, the statistical calculation showed that the results of to (t-observation) was greater than tt (t-table) in which to obtain was 19.24 while the value of t-t was 2.015 with a significant level of 5% (0.05). Therefore, alternative hypothesis (Ha) was accepted while null hypothesis was rejected. This research summarized that 9GAG application has a positive effect to improve students’ speaking skills.